Enzyme replacement therapy for late‐onset Pompe disease - Sharma, Reena (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of ERT in people with LOPD.